VHH-Based Bispecific Antibodies Targeting Cytokine Production - Nosenko, Maxim A.; Atretkhany, Kamar-Sulu N.; Mokhonov, Vladislav V.; Efimov, Grigory A.; Kruglov, Andrey A.; Tillib, Sergei V.; Drutskaya, Marina S.; Nedospasov, Sergei A. (Frontiers in Immunology, 2017)
Proinflammatory cytokines, such as TNF, IL-6 and IL-1, play pathogenic roles in multiple diseases and are attractive targets for biologic drugs. Because proinflammatory cytokines possess non-redundant protective and immunoregulatory functions, their systemic neutralization carries the potential for unwanted side effects. Therefore, next-generation anti-cytokine therapies would seek to selectively neutralize pathogenic cytokine signaling, leaving normal function intact. Fortunately, the biology of proinflammatory cytokines provides several such opportunities. Here we discuss various applications of bispecific antibodies targeting cytokines with specific focus on selective TNF neutralization targeted directly to the surface of specific populations of monocytes and macrophages. These bispecific antibodies combine an anti-TNF VHH with VHHs or scFvs directed against abundant surface molecules on myeloid cells, and serve to limit the bioavailability of TNF produced by these cells. Such reagents may become prototypes of a novel class of anti-cytokine biologics.